Research note: Spatial variations of condition class in Clifty Wilderness, Daniel Boone National Forest, KY, USA. (December 2022) - Kim, Min-Kook; Kim, Jinwon; Sharp, Ryan
Abstract: The purpose of this study was to explore spatially heterogeneous relationships between campsite condition class and its associated variables in Clifty Wilderness, Daniel Boone National Forest, KY, USA. To account for local dynamics, we used a geographically weighted regression (GWR) model, which has rarely been applied in previous recreation resource monitoring research. The GWR model effectively visualized local variations in modeling the campsite condition class, with improvements in model performance over the corresponding ordinary least squares model. Findings of this study could contribute to exploring spatial variations of condition class, ultimately providing guidelines for location-based park and protected area management. Management implications: The findings of this study could play an important role in facilitating guidelines for location-based park and protected area management.